Guernsey-Crown Dependency of the United Kingdom : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2003)
The financial services sector plays a dominant role in the economy of Guernsey. The report is organized in two volumes. Volume I provides the findings and the Reports on the Observance of Standards and Codes (ROSCs). Volume II provides the detailed assessments of the Basel Core Principles for Effective Banking Supervision, the insurance core principles, the objectives and principles of securities regulation, and the financial action task force recommendations, as well as a review against the Offshore Group of Banking Supervisors (OGBS) statement of best practice for trust and company service providers.